‚Gelobtes Land‘ - Meineke, Eva-Tabea; Neu-Wendel, Stephanie; Liermann Traniello, Christiane; Zeiger, Carina; Hertrampf, Marina Ortrud M.; Izzo, Sara; Hammoudi, Rafika; Almeida (†), Dimitri; von Hagen, Kirsten; Snelling-Gogh, Rosemary (Akademische Verlagsgemeinschaft München (AVM), 2025)
In today's secularised Europe with its pluralistic societies, a renewed, intense and conflict-laden interest in religion can be observed: especially since the confrontation of the “Christian West” with migration movements from the Global South, which has been accompanied by a pluralisation of denominational affiliations - with a simultaneous continuing wave of church resignations and criticism of the churches - but also due to the confrontation with Islamist terror and the associated fear of radicalisation. Against this background, this volume poses the question from a diachronic perspective of the epistemological potential of the examination of religion(s) in the literatures and cultural forms of expression of Romania, their contribution to discursive diversity and the function of the “sacred”, of sacrality with regard to sustainable European identity constructions. The thematic fields within which the significance of religion and spirituality are explored are national and European cohesion on the one hand and the discourses of marginalisation on the other, the relationship between Europe and Islam and the mutual condition of spirituality and aesthetics.